Contemporary Nomenclatures of Suicidal Behaviors: A Systematic Literature Review. Issue 3 (9th May 2017) - Goodfellow, Benjamin; Kõlves, Kairi; de Leo, Diego
Abstract : Addressing the lack of comparability of research results around the world, a systematic literature review of existing nomenclatures was conducted. After distinguishing the concepts of nomenclature and classification, 13 contributions to nomenclature of suicidal behavior are described and summarized using outcome and intent as guiding concepts for analysis. The issue of what is being defined in nomenclatures is fundamental and impacts the way intent and outcome are used. The existing confusion between classification and nomenclature stems from conflicting purposes of the nature of definition; that is, to communicate concepts versus to be descriptive of reality.